The ANTIHYPERGLYCEMIC ACTIVITY OF SYNBIOTIC EXTRACT FROM JICAMA (Pachyrhizus erosus) and Lactobacillus acidophilus IN HYPERGLYCEMIC MICE (Mus musculus) - Eki Herawati; Iis Herawati; Ida Wiryanti (LPPM Universitas Abdurrab, 2025)
The increase in the prevalence of diabetes mellitus has prompted the search for complementary therapies based on natural ingredients. Jicama (Pachyrhizus erosus) is a source of inulin, which has been shown to act as a prebiotic. Lactobacillus acidophilus, on the other hand, is classified as a probiotic and has been demonstrated to maintain the balance of gut microbiota. The combination of these two substances as a synbiotic is expected to have a synergistic effect in lowering blood glucose levels.The objective of this study is to examine the antihyperglycemic effects of administering a synbiotic extract of jicama and L. acidophilus to mice (Mus musculus) with hyperglycemia.The experimental design of the study comprised four distinct treatment groups: a control group, a group exposed to a single dose of bengkuang extract, a group exposed to a single dose of L. acidophilus, and a group exposed to a synbiotic combination. Hyperglycaemia was induced by administering streptozotocin at a dose of 55 mg/kg BW. The parameters measured included blood glucose levels. Statistical data analysis was performed using a paired t-test (Paired t-test). The synbiotic combination demonstrated a substantial reduction in blood glucose levels in hyperglycemic mice (p=0.04442). Conversely, the jicama extract group exhibited no statistically significant effect (p=0.12287) when compared to the control group. However, a decline in blood glucose levels from 285.50 mg/dL to 223.50 mg/dL was observed when the data was examined from the average before and after treatment perspectives. The administration of L. acidophilus suspension to hyperglycemic mice (Mus musculus) demonstrated no significant impact on blood glucose levels (p=0.05213), while the control group administered with distilled water exhibited a significant increase in blood glucose levels (p=0.00085) from an average of 114.25 mg/dL to 145.25 mg/dL.The synbiotic combination of jicama extract and Lactobacillus acidophilus has demonstrated potential as an antihyperglycemic agent, operating through mechanisms that include improving glucose metabolism, increasing glucose transporter expression, and modulating the gut microbiota. This formulation has the potential to be developed as a functional food-based adjunct therapy.